Report of Meeting. The Twentieth Debrecen-Katowice Winter Seminar on Functional Equations and Inequalities Hajdúszoboszló (Hungary), January 29-February 1, 2020 - AMSil, Redakcja (Annales Mathematicae Silesianae, 2020)
Report of Meeting. The Twentieth Debrecen-Katowice Winter Seminar on Functional Equations and Inequalities Hajdúszoboszló (Hungary), January 29-February 1, 2020.